PERFORMANCE ANALYSIS OF OSPF AND RIP ROUTING METHODS WITH TRAFFIC ENGINEERING USING CISCO PACKET TRACER IN NETWORK ARCHITECTURE - Maulina Sari, Elsa; Aisya Putri, Sabila; Maylunna Ratu Sedyo Putri, Salsha; Winarno, Sinyoardi (Indonesian Journal of Electrical Engineering and Electronics, 2023)
The development and utilization of computer networks have experienced rapid growth in recent years. Many organizations and offices now rely on computer networks as their primary means of carrying out tasks. This research aims to analyze the performance of two dynamic routing methods, OSPF and RIP, in the network architecture at Universitas Pembangunan Nasional Veteran Jakarta.In this study, OSPF uses the smallest cost value as the best route, while RIP uses the closest distance between nodes as the best route to reach the destination host. Furthermore, this research conducts testing on Quality of Service (QoS) parameters such as delay, packet loss, and throughput to determine the most suitable method. The testing is conducted in two scenarios: when the network is not busy and when the network is busy. Additionally, there are three testing stages: when all network connections are established, when one route is disconnected, and when two routes are disconnected between routers.The test results show that the best method is RIP with an average delay of 4.7 ms, 0% packet loss, and a throughput of 163.156 Kbps when the network is not busy. On the other hand, when the network is busy, the best method is RIP with an average delay of 16.9 ms, 0% packet loss, and a throughput of 23.006 Kbps.